Breeding and feeding habitat selection by an island endemic bird may increase its vulnerability to climate change. (18th November 2020) - Radley, Paul M.; van Etten, Eddie J. B.; Blake, David; Davis, Robert A.
Abstract: Characterizing patterns of habitat use is an important first step for effective conservation planning. Species restricted to low‐lying islands are at greatest risk from climate change‐related sea level rise, and requirements for breeding and foraging habitat may determine their risk from tidal inundation. The endangered Micronesian Scrubfowl ( Megapodius laperouse senex ) is a model species for understanding these impacts. This species faces the cumulative challenges of tourist visitation, invasive species, and rising sea levels, yet little is understood about its habitat use in the Rock Islands Southern Lagoon Conservation Area (RISL) of Palau. We studied the habitat requirements of this mound‐nesting scrub‐fowl as a representative of a group of birds considered highly vulnerable to climate change. Analysis of 15 habitat variables at 24 incubation mounds and 26 randomly chosen sites indicated that scrubfowl selected incubation sites that were close to shore, contained large trees, and exhibited greater canopy heights than the surrounding forest. Birds preferentially built mounds at the base of large ironwood trees ( Casuarina equisetifolia ) but selected sites with significantly more breadfruit trees ( Artocarpus mariannensis ) than random. Scrubfowl foraged in a non‐preferential manner, making use of all littoral strand forest habitat. Direct anthropogenic habitat loss is not a major threat to scrub‐fowl in the RISL, but their breeding habitat is highly vulnerable to climate change‐driven sea level rise. Abstract : Micronesian Scrubfowl in Palau are an endangered species with rising sea levels a key threat to their restricted feeding and foraging habitat. We sought to characterise nesting and foraging habitat in the Rock Islands Southern lagoon of the Republic of Palau. Birds preferentially built mounds at the base of large ironwood trees (Casuarina equisetifolia) but selected sites with significantly more breadfruit trees (Artocarpus mariannensis) than random. Scrubfowl foraged in a non‐preferential manner, making use of all littoral strand forest habitat.